Calculation:

Consider the following function

\(\displaystyle{k}{\left({x}\right)}=-{5}{x}+{1}\)

For x-intercept put \(\displaystyle{k}{\left({x}\right)}={0}\)

\(\displaystyle{0}=-{5}{x}+{1}\)

\(\displaystyle{5}{x}={1}\)

\(\displaystyle{x}={\frac{{{1}}}{{{5}}}}\)

Hence, the x-intercept is at \(\displaystyle{\left({\frac{{{1}}}{{{5}}}},{0}\right)}\)

For y-intercept put \(\displaystyle{x}={0}\)

\(\displaystyle{k}{\left({0}\right)}=—{5}{\left({0}\right)}+{1}={1}\)

Hence, the y-intercept is at (0, 1)

Consider the following function

\(\displaystyle{k}{\left({x}\right)}=-{5}{x}+{1}\)

For x-intercept put \(\displaystyle{k}{\left({x}\right)}={0}\)

\(\displaystyle{0}=-{5}{x}+{1}\)

\(\displaystyle{5}{x}={1}\)

\(\displaystyle{x}={\frac{{{1}}}{{{5}}}}\)

Hence, the x-intercept is at \(\displaystyle{\left({\frac{{{1}}}{{{5}}}},{0}\right)}\)

For y-intercept put \(\displaystyle{x}={0}\)

\(\displaystyle{k}{\left({0}\right)}=—{5}{\left({0}\right)}+{1}={1}\)

Hence, the y-intercept is at (0, 1)